Projects in the Computing Curriculum
XV, 231 p. 9 illus.
Keywords: Dr Peter Milton, Director of Programme Review, Quality Assurance Agency I am grateful to the authors for giving me the opportunity to write this foreword, mainly because it represents the first occasion that the Fund for the Development of Teaching and Learning (FDTL) has led directly to a pUblication such as this. In my former capacity as Director of Quality Assessment at the Higher Education Funding Council for England (HEFCE), I chaired the FDTL Committee during 1996/7 and am delighted to see the projects which were selected so painstakingly leading to successful outcomes. Assessment of the quality of higher education (HE) was introduced in 1993 and was intended to improve public information about what was on offer in British universities and colleges, as well as to assist in the enhancement of educational opportunities for students. This was part of a larger agenda in which educational quality and the standards achieved by students have come under increasing scrutiny, with a long-term objective of linking funding allocations to the quality of the provision. It was in this context that the FDTL Initiative was launched in 1995 to support projects aimed at stimulating developments in teaching and learning and to encourage the dissemination of good practice across the HE sector. Good practice is identified through the process of quality assessment and bids for funding can only be made by those institutions which have demonstrated high quality provision. To date, the programme includes 63 projects drawn from 23 subject areas.